Effect of indomethacin, diclofenac sodium and sodium salicylate on peripheral blood cell counts in sublethally gamma-irradiated mice - Pospísil, M; Netíková, J; Kozubík, A; Pipalová, I (Strahlentherapie und Onkologie, 1989)
Treatment with indomethacin and diclofenac sodium was found to increase granulocyte counts in the blood of sublethally gamma-irradiated mice. Treatment with sodium salicylate was ineffective in this respect, administration of sodium salicylate together with indomethacin even decreased the indomethacin-induced effects. The results suggest that the hemopoiesis-stimulating effects of non-steroidal anti-inflammatory drugs cannot be correlated with the anti-inflammatory activity but rather with the side effects of these compounds, including the action on gastro-intestinal prostanoid production. This conclusion doubts on the possibility of the usefulness of non-steroidal anti-inflammatory drugs in conditions of the radiation syndrome.
Keywords: krevní obraz; Animals; vztah mezi dávkou a účinkem léčiva; salicylan sodný; diklofenak; indomethacin; Radiation Injuries, Experimental; Time Factors; časové faktory; Indomethacin; Mice; myši; Hematopoiesis; Dose-Response Relationship, Drug; Male; Mice, Inbred CBA; experimentální radiační poranění; Diclofenac; hematopoéza; zvířata; mužské pohlaví; myši inbrední CBA; Mice, Inbred C57BL; Sodium Salicylate; Blood Cell Count; myši inbrední C57BL